A BIOBASED NANO/MICRO-STRUCTURED MATERIAL FOR MICROORGANISMS' IMMOBILIZATION - Armanu, Emanuel Gheorghita; Secula, Marius Sebastian; Cimpoesu, Nicanor; Heipieper, Hermann J; Volf, Irina (International Multidisciplinary Scientific GeoConference SGEM, 2024)
Microbial immobilization is a promising strategy for various applications, including environmental remediation and bioprocess engineering. However, the efficacy of immobilization largely depends on the characteristics of the carriers. Biomass wastes are renewable and abundant resources that can be subjected to hydrothermal carbonization (HTC) for hydrochar production, a resulting carbonaceous material with a porous structure. This porous architecture offers extensive surface area and facilitates the colonization and growth of microorganisms, working as a protective buffer zone in highly polluted environments. This study points out the development of a novel biobased nano/micro-structured material for microorganism immobilization, integrating locally available feedstock for thermochemical conversion processes. To tailor a bio-based porous material suitable for bacterial immobilization, the biomass waste was processed through HTC. The influence of main HTC parameters on biomass conversion was established. Chemical, structural, and thermochemical analyses, encompassing proximate and ultimate analysis, Fourier Transform Infrared Spectroscopy (FTIR), Scanning Electron Microscopy (SEM), Chemical Composition Analyzer (EDS) and Thermogravimetric analysis (TGA), were conducted on both the feedstock and resulting hydrochar. SEM analyses revealed the nano/micro-structured morphology of the hydrochar, characterized by a wide distribution of pores ranging from nano to micrometer scale. A bacterial strain of Pseudomonas sp. was immobilized on hydrochar in order to evaluate the bacterial cell proliferation, their capacity and rate of forming stable colonies on the support material. The hydrochar obtained from locally biomass feedstocks represents an eco-friendly and sustainable biobased nano/micro-structured material, with promising applications in bioremediation and bioprocess engineering, thereby advancing green technologies and circular bioeconomy initiatives.